2018
DOI: 10.1093/gastro/goy005
|View full text |Cite
|
Sign up to set email alerts
|

Extra-pancreatic complications, especially hemodialysis predict mortality and length of stay, in ICU patients admitted with acute pancreatitis

Abstract: Background and aimsPatients in the intensive care unit (ICU) with acute pancreatitis (AP) are at risk for extra-pancreatic complications given their severe illness and prolonged length of stay. We sought to determine the rate of extra-pancreatic complications and its effect on length of stay (LOS) and mortality in ICU patients with AP.MethodsWe performed a retrospective cohort study of ICU patients admitted to a tertiary-care center with a diagnosis of AP. A total of 287 ICU patients had a discharge diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…The mortality rate in our cohort was similar to that previously reported [6, 8, 9, 23]. Patients who received delayed AIT had poorer outcomes in terms of morbidity, nosocomial infections and length of ICU stay, despite a less severe clinical status on admission.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mortality rate in our cohort was similar to that previously reported [6, 8, 9, 23]. Patients who received delayed AIT had poorer outcomes in terms of morbidity, nosocomial infections and length of ICU stay, despite a less severe clinical status on admission.…”
Section: Discussionsupporting
confidence: 87%
“…In another large cohort of 173 infected patients with AP, Besselink et al reported 98 (57%) cases of infected necrosis and 84 (49%) cases of pneumonia, but these rates were reported for the entire stay [23]. In another retrospective study focusing on extrapancreatic complications in ICU patients with AP, infectious complications were observed in 56/103 (54%) patients with a predominance of respiratory and urinary tract infections (43% and 21.5% of all infectious complications, respectively) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Our study follows our previous report on all EPCs in patients admitted to the ICU with AP 13 . Furthermore, it corroborates the results of previous studies demonstrating the impact of infectious EPCs, which reported bacteremia, UTIs, and respiratory infections being the most common infections 12,16–18 .…”
Section: Discussionsupporting
confidence: 92%
“…Not surprisingly, GI bleeding was an independent predictor of LOS as seen in previous studies. 13 In our study, we demonstrate that 1 in 5 patients with mild AP will have an EPC, which contributes to the LOS. Patients with mild AP typically have minimal symptoms and, in many cases, can improve within 24 hours.…”
Section: Discussionmentioning
confidence: 48%
“…However, LNR was not incorporated into our prediction model due to the different tumor type, the larger cohort in our study, and different statistical approach. Notably, more than 6 h of operating time, more than 1 month stay in hospital, and more severe complications (Clavien-Dindo Grade >1) tend to indicate complicated surgery [43][44][45][46], and the complexity of surgery is often positively associated with tumor malignancy. Most malignant tumors can invade the important organs and blood vessels nearby, which greatly increases the difficulty of surgery and worsens the prognosis.…”
Section: E918882-8mentioning
confidence: 99%